1997
DOI: 10.1108/09590559710156071
|View full text |Cite
|
Sign up to set email alerts
|

UK retailers and AIDS ‐ an exploratory study

Abstract: Examines UK retailers' attitudes towards employee welfare in general, and the development and implementation of policies in respect of staff with HIV/AIDS in particular. From the research results, provides a valuable insight into retailer motivation in respect of staff welfare provision and the methods adopted by retailers in the development of welfare policy; identifies the need to ensure that a credible support strategy exists in order that welfare policies, such as those related to HIV/AIDS, can be implemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

1998
1998
2000
2000

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…The self‐declared ‘uncaring’ employers observed that welfare was ‘not a high priority’. Some respondents especially noted ‘a possible welfare hierarchy’ whereby the retailer's assistance to an individual would depend on the company's position on the subject, which is consistent with previous research by McLean and Moore 23 . In terms of actual practice, respondents were asked whether the company would consider offering employee assistance and if so, what type of assistance should be provided, if an employee contracted HIV/AIDS.…”
Section: Welfare/eapsupporting
confidence: 53%
See 1 more Smart Citation
“…The self‐declared ‘uncaring’ employers observed that welfare was ‘not a high priority’. Some respondents especially noted ‘a possible welfare hierarchy’ whereby the retailer's assistance to an individual would depend on the company's position on the subject, which is consistent with previous research by McLean and Moore 23 . In terms of actual practice, respondents were asked whether the company would consider offering employee assistance and if so, what type of assistance should be provided, if an employee contracted HIV/AIDS.…”
Section: Welfare/eapsupporting
confidence: 53%
“…Marchington and Wilkinson 22 relate that even when ‘best practice’ appears to be adopted, it is often implemented without clear and careful planning, and taken up as the latest fad or fashion, without considering how it might actually contribute to competitive advantage. The authors observed this phenomenon in a previous study 23 which identified that development of some retailers’ HIV/AIDS policies were in response to ‘public image concerns’ and more about ‘joining the Liz Taylor bandwagon’ than determining the practical implications of having such a policy.…”
Section: Hr Policymentioning
confidence: 89%
“…18 Marchington and Wilkinson 22 relate that even when 'best practice' appears to be adopted, it is often implemented without clear and careful planning, and taken up as the latest fad or fashion, without considering how it might actually contribute to competitive advantage. The authors observed this phenomenon in a previous study 23 which identified that development of some retailers' HIV/AIDS policies were in response to 'public image concerns' and more about 'joining the Liz Taylor bandwagon' than determining the practical implications of having such a policy.…”
Section: Hr Policymentioning
confidence: 89%
“…Some respondents especially noted 'a possible welfare hierarchy' whereby the retailer's assistance to an individual would depend on the company's position on the subject, which is consistent with previous research by McLean and Moore. 23 In terms of actual practice, respondents were asked whether the company would consider offering employee assistance and if so, what type of assistance should be provided, if an employee contracted HIV/AIDS. The results are shown in Table 3.…”
Section: Welfare/eapmentioning
confidence: 99%